Treatment with the flavonoid 7, 8-Dihydroxyflavone: a promising strategy for a constellation of body and brain disorders. Issue 1 (2nd January 2022) - Emili, Marco; Guidi, Sandra; Uguagliati, Beatrice; Giacomini, Andrea; Bartesaghi, Renata; Stagni, Fiorenza
Abstract: Flavonoids have long been known to exert benefits in various health problems. Among them, the BDNF mimetic 7, 8-Dihydroxyflavone (7, 8-DHF) is emerging as a potential treatment for a constellation of brain and body pathologies. During the past 10 years, more than 180 preclinical studies have explored the efficacy of 7, 8-DHF in animal models of different pathologies. The current review intends to be an exhaustive survey of these studies. By providing detailed information on the rationale of the experimental design and outcome of treatment, we will give the reader tools to critically interpret the achievement obtained so far. If we put together each individual piece of this complex mosaic, a picture emerges that is full of promise regarding the potential usefulness of 7, 8-DHF for human treatment. Much has been done so far and we believe that the time is now ripe to move from the bench to the bedside, in order to establish whether supplementation with 7, 8-DHF may serve as therapy or, at least, as adjuvant for the treatment of pathologies affecting brain and body functioning.